1995
DOI: 10.1111/j.1365-2249.1995.tb03793.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelic polymorphism in IL-1β and IL-1 receptor antagonist (IL-1Ra) genes in inflammatory bowel disease

Abstract: SUMMARY Recent reports have shown that allele 2 of the IL‐1 receptor antagonist (IL‐1Ra) gene is over‐represented in ulcerative colitis (UC). Healthy individuals carrying allele 2 of this gene have increased production of IL‐1Ra protein. Since the final outcome of the biological effects of IL‐1β may depend on the relative proportion of these two cytokines, we have studied if a TaqI polymorphism in the IL‐1β gene, which is relevant to IL‐1β protein production, may be involved in the genetic susceptibility to UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(60 citation statements)
references
References 27 publications
6
49
1
4
Order By: Relevance
“…25,26) Others have suggested that this SNP may interrupt the IL-1β production regulation mechanism or decrease the level of IL-1ra, which will then increase the production or in vivo activities of IL-1β. 27) Surprisingly, our findings were contradictory with a few preceeding studies investigating the association between IL-1β and the onset of SLE in different populations. In a study carried out by Parks and his collaborators based on a Caucasian population in southeast of the United States, it was revealed that the −511 C/T was significantly associated to SLE.…”
Section: Analysis Of the Il-1β −511 C/t Polymorphismscontrasting
confidence: 99%
“…25,26) Others have suggested that this SNP may interrupt the IL-1β production regulation mechanism or decrease the level of IL-1ra, which will then increase the production or in vivo activities of IL-1β. 27) Surprisingly, our findings were contradictory with a few preceeding studies investigating the association between IL-1β and the onset of SLE in different populations. In a study carried out by Parks and his collaborators based on a Caucasian population in southeast of the United States, it was revealed that the −511 C/T was significantly associated to SLE.…”
Section: Analysis Of the Il-1β −511 C/t Polymorphismscontrasting
confidence: 99%
“…These same genes may now confer selective disadvantages in modern times, particularly given the average life span increases, environmental stresses, and western diet/lifestyle that could lead to insulin resistance and atherosclerosis [156][157][158].…”
Section: Genetic Susceptibility and Inflammatory Gene Polymorphisms Imentioning
confidence: 99%
“…IL-1b ?5887 polymorphism alters IL-1b production following lipopolysaccharide (LPS) stimulation in vitro [36]. However, IL-1b ?5887 genotype was not significantly different between patients and controls [36][37][38][39][40]. IL-1b ?5887 did not have a significant association with anatomic location of the disease [39,40].…”
Section: Discussionmentioning
confidence: 99%